(untitled) (International Journal of Engineering Sciences & Management Research, 2014)
On the basis of Zel’dovich–von Neumann–Doering detonation theory with allowance for the theory of chain processes by the example of the oxidation of hydrogen-rich mixtures in the presence of an inhibitor, it is shown that taking into account inhibition reactions leads to the occurrence of “chemical” losses in addition to heat losses. “Chemical” losses alone can provide the occurrence of concentration limit of detonation; the velocity of the combustion wave near the limit is supersonic. Theoretical estimates agree qualitatively with the experimental data on the inhibition of a developing detonation wave in H2 –air mixtures with additives of propane–butane mixture (0.5–4%) at 1 atm.